PDRI DALAM KARYA SENI LUKIS - Emasyah Andika Putra; Erfahmi Erfahmi (Universitas Negeri Padang, 2021)
The purpose of this painting with the PDRI idea is to visualize a heroic event that is starting to be forgotten. The method of creating painting works through stages (1) Preparation, (2) Elaboration, (3) Synthesis, (4) Realization of concepts, and (5) completion. Ten paintings about heroic events of PDRI were created. The whole work tells about the synergy between the community guerrillas and the PDRI to expel the Dutch and gain Indonesian sovereignty. This painting is an interesting medium to identify the history of PDRI. Besides, this work is also expected to be a motivation in appreciating the history of the Indonesian nation.Keywords: PDRI, Indonesian Republic,art painting